2005
DOI: 10.1111/j.1463-1318.2005.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative arrhythmias in colorectal surgical patients: incidence and clinical correlates

Abstract: Arrhythmias are common following elective large bowel resection. They occur in older patients and are associated with the development of other complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 30 publications
6
50
0
5
Order By: Relevance
“…The reported incidence ranges from 0.37% 9 to 20%. 4,5 Christians et al 9 reported that atrial fibrillation (AF) affected only 0.37% in a cohort of over 13,000 patients. However, the series was retrospective and included patients undergoing orthopaedic and ophthalmic procedures as well as relatively minor procedures such as hernia repair and appendicectomy.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence ranges from 0.37% 9 to 20%. 4,5 Christians et al 9 reported that atrial fibrillation (AF) affected only 0.37% in a cohort of over 13,000 patients. However, the series was retrospective and included patients undergoing orthopaedic and ophthalmic procedures as well as relatively minor procedures such as hernia repair and appendicectomy.…”
Section: Incidencementioning
confidence: 99%
“…The reported incidence following major non-cardiothoracic surgery ranges from 4-20%, depending on the type of surgery performed, the degree of cardiac monitoring undertaken and the type of arrhythmia studied. [4][5][6][7][8] The majority of patients included in these series were undergoing major abdominal or vascular surgery. Non-vascular abdominal surgery has been identified as an independent risk factor for postoperative supraventricular arrhythmias (SVAs).…”
mentioning
confidence: 99%
“…However, most of the previous studies related to new onset SVA/AF incidence and outcomes in critical illness come from a heterogeneous population of mixed medical, surgical and trauma patients. 4,[6][7][8]10,[20][21][22][23] Moreover, unlike previous studies, our study examined a cohort of African American medical ICU patients and importantly excluded surgical, trauma and postcardiotomy patients with severe sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…4 Fluid-related complications, such as electrolytes imbalance or fluid overload, may occur in up to 54% of patients undergoing major abdominal surgery. 5,6 This is especially so in the elderly and those prescribed excess sodium or fluid volume.This, in turn, leads to a longer hospital stay and unplanned critical care unit admission. It may delay return of gastrointestinal function and contribute to complications such as anastomotic leak.…”
Section: 4mentioning
confidence: 99%